Analisis Akuntabilitas Pengelolaan Alokasi Dana Desa Kenagarian Sarilamak Kecamatan Harau Kabupaten Lima Puluh Kota Tahun 2022 -2023 - Shelby Yuliarni Putri; Rika Widianita (ARZUSIN, 2026)
The management of Village Fund Allocation (ADD) requires the adequate implementation of accountability, but at the nagari level, problems are still found in the form of discrepancies in budget realization, increasing SILPA, and low Village Own-Source Revenue (PAD). This study aims to analyze the implementation of accountability in the management of ADD in Nagari Sarilamak based on five indicators of village financial management, namely planning, implementation, administration, reporting, and accountability, as well as to identify the constraints in its implementation. This study employed a descriptive qualitative approach with data collection techniques through interviews, observation, documentation, and literature study. The research informants consisted of the wali nagari, nagari officials, and the community. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the principle of accountability had been implemented, but not yet optimally. At the planning stage, the process had been carried out through tiered deliberation, although two-way communication was still limited. At the implementation stage, activities had involved the community, but often experienced delays that affected the emergence of SILPA. At the administration stage, management had utilized the SISKEUDES application, but was still constrained by network problems and low PAD. Meanwhile, reporting and accountability had been carried out in accordance with the provisions, but were often hindered by regulatory changes. These findings indicate that the management of ADD in Nagari Sarilamak has reflected transparency and participation, but still requires improved efficiency, strengthened PAD, and better communication and public oversight so that accountability in village financial management can be implemented more optimally.